Unc93b1 is essential for cytokine activation of five PAMPs in the orange-spotted grouper (Epinephelus coioides). (April 2018) - Liang, Yaosi; Wang, Yu; He, Liangge; He, Jianan; Peng, Wan; Zhou, Libin; Zhang, Yong; Zhang, Haifa; Shi, Herong; Lin, Haoran; Lu, Danqi
Abstract: Toll-like receptors (TLRs) are important innate immune receptors that recognize multiple pathogen-associated molecular patterns (PAMPs) and activate the immune responses to resist the invasion of pathogens. Many TLRs need assistance from trafficking chaperones to transport to the specific cell compartments and then are processed before they are activated. In this study, we identified an important trafficking chaperone, Unc-93 homolog B1 ( unc93b1 ), from the Epinephelus coioides (orange-spotted grouper). The deduced protein sequence of Eco.unc93b1 was 632 amino acids, containing 12 transmembrane domains, consistent with other UNC93B1 proteins from other species. Phylogenetic analysis showed that Eco. Unc93b1 was clustered with teleost Unc93b1 and had the closest relationship with Larimichthys crocea (large yellow croaker) Unc93b1. Eco.unc93b1 was expressed the highest in the spleen, and its protein was co-localized with the endoplasmic reticulum and early endosomes in both human embryonic kidney 293T cells and grouper spleen cells (GS cells). Moreover, the stimulation of lipopolysaccharide (LPS), high-molecular-weight poly (I:C) (HMW), imidazoquinoline (R848), polyadenylic-polyuridylic acid (poly AU), and 19-mer Staphylococcus aureus 23S rRNA-derived oligoribonucleotide (ORN Sa 19) promoted the mRNA expression of unc93b1 in GS cells with different patterns. Furthermore, the cytokine expression induced by these PAMPs was suppressed, while Eco.unc93b1 was knocked down, by small interfering RNA. In conclusion, these results suggest that Eco.unc93b1 plays an essential role in several PAMP-induced immune responses. Highlights: The Eco. Unc93b1 was co-localized with the endoplasmic reticulum and early endosomes. The expression of Eco. Unc93b1 could be up-regulated by five PAMPs in different patterns. Five PAMPs induced production of cytokines is Eco. Unc93b1 independent.